PKM PEMANFAATAN TEKNOLOGI POMPA SUBMERSIBLE DI DESA PADANGDANGAN KECAMATAN PASONGSONGAN KABUPATEN SUMENEP JAWA TIMUR - Sutrisno, Adi; Mustakim, '; andayani, sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Padangdangan Village is one of the villages that lacks irrigation water when the dry season arrives. This is caused by the soil structure is included in dry land which can only be planted with corn, once a year. Padangdangan villagers rarely have their own toilets, so for the need to defecate, most villagers do it in open fields. This causes an outbreak of unwanted diseases. With this problem, the PKM program was offered entitled